Is an Oral Glucose Tolerance Test Still Valid for Diagnosing Diabetes Mellitus? - Dong-Lim Kim; Sun-Doo Kim; Suk Kyeong Kim; Sooyoun Park; Kee-Ho Song (Diabetes & Metabolism Journal, 2016)
BackgroundWe evaluated the diagnostic rate of diabetes using fasting plasma glucose (FPG), 2-hour plasma glucose (2h PG) after 75 g oral glucose tolerance test (OGTT), and glycosylated hemoglobin (HbA1c) levels, and we elucidated the pathophysiologic characteristics and risk factors that give rise to diabetes in patients with prediabetes.MethodsThe data of 236 patients who had the OGTT at Konkuk University Hospital were analyzed. Fasting, 30, and 120 minutes blood glucose levels and insulin levels were measured. The diagnostic rate of diabetes was assessed using FPG, 2h PG, and HbA1c levels. The clinical data and insulin resistance and secretion evaluations were compared using indexes according to the fasting glucose level.ResultsAmong 236 subjects, 97 (41.1%) were diabetics and 102 (43.2%) were prediabetics. The rate of diabetes diagnosis by one of the individual criteria was 56.7%, 53.6%, and 84.5% for FPG, HbA1c, and 2h PG, respectively. When two criteria were used to diagnose diabetes, 72.2% of the diabetic patients were identified by FPG and HbA1c, while 100% were identified by FPG and 2h PG, and 91.7% were identified by 2h PG and HbA1c. The HbA1c cut-off value for 2h PG ≥200 mg/dL was 6.1%, and the FPG cut-off value was 115 mg/dL. In impaired fasting glucose subjects, the HbA1c level, Matsuda index, and insulinogenic index were associated with risk of occurrence of overt diabetes (P<0.01).ConclusionThis study suggests that performing additional OGTT for patients with FPG ≥110 mg/dL or HbA1c ≥6.1% is helpful to reclassify their glucose tolerance status and evaluate their potential for progressing to overt diabetes.